Psychological contract breach and happiness at work in healthcare sector: Double mediation of colleague support and deviant workplace behaviour - Saadia Qaiser; Ghulam Abid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The study examines the association between psychological contract breach (PCB) and happiness at work and the double mediating role of colleague support and deviant workplace behaviour on the relationship of PCB and happiness at work. structural equation modeling (SEM) has been used to analyze the data of 401 questionnaires from the health sector of Lahore, Pakistan. The study discovered support for the negative relationship between PCB and happiness at the workplace. However, colleague support is reduced in the manifestation of a PCB that reduces happiness at work. Similarly, deviant workplace behaviour has been increased in the presence of psychological contract breaches, causing a reduction in happiness at work. The data for the study was conducted during the time of Pandemic COVID19, where there was an immense level of pressure on the health sector, keeping in mind that schedules of doctors and nurses had been extremely stressful, collection of data and responses was challenging. The input of the study is the incorporation of conservation of resource theory (COR) and social exchange theory (SET) during the pandemic situation. The research also provides both theoretical and practical implications and suggests future areas for supplementary studies.
Keywords: 330; psychological contract breach; happiness at work; colleague support; deviant workplace behaviour; health care sector; Pakistan